2019
DOI: 10.1007/s13311-019-00734-3
|View full text |Cite
|
Sign up to set email alerts
|

At-Home Cortical Stimulation for Neuropathic Pain: a Feasibility Study with Initial Clinical Results

Abstract: The clinical use of noninvasive cortical stimulation procedures is hampered by the limited duration of the analgesic effects and the need to perform stimulation in hospital settings. Here, we tested the feasibility and pilot efficacy of an internet-based system for at-home, long-duration, medically controlled transcranial motor cortex stimulation (H-tDCS), via a double-blinded, shamcontrolled trial in patients with neuropathic pain refractory to standard-of-care drug therapy. Each patient was first trained at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…In a current randomized in parallel double-blinded design, with adults' females with fibromyalgia allocated 2:1 to receive a-tDCS or sham tDCS for four weeks (20 sessions) we found that the adherence verified by the records on the software in the active-tDCS was 91.71% (n=28), while that received sham-tDCS was 98.51%(n=14) [152]. In addition, the studies with tDCS at home have found only minor adverse effects with an incidence comparable to the ones described in the literature when the treatment is applied under direct supervision [23,150,151].…”
Section: Home-based Tdcsmentioning
confidence: 90%
See 1 more Smart Citation
“…In a current randomized in parallel double-blinded design, with adults' females with fibromyalgia allocated 2:1 to receive a-tDCS or sham tDCS for four weeks (20 sessions) we found that the adherence verified by the records on the software in the active-tDCS was 91.71% (n=28), while that received sham-tDCS was 98.51%(n=14) [152]. In addition, the studies with tDCS at home have found only minor adverse effects with an incidence comparable to the ones described in the literature when the treatment is applied under direct supervision [23,150,151].…”
Section: Home-based Tdcsmentioning
confidence: 90%
“…They rated daily pain daily during 11 consecutive weeks, and afterward via iterative visits/phone contacts. Patients achieved satisfactory relief on a scale combining pain scores, drug intake, and quality of life [150]. In another randomized study, we evaluate the feasibility of tDCS at home for 10 days (10 sessions) in 20 healthy subjects (8 men /12 women).…”
Section: Home-based Tdcsmentioning
confidence: 99%
“…There has been a growing interest to employ home-based tDCS as an intervention for a wide array of clinical conditions, research so far has been done on conditions ranging from neuropathic pain (Garcia-Larrea et al, 2019) to Multiple Sclerosis (Charvet et al, 2017). The described remote training program could be adapted to clinical contexts beyond depression.…”
Section: Discussionmentioning
confidence: 99%
“…Although active tDCS over the contralateral M1 (1.4 mA, 30 min) was administered for 5 consecutive days, no significant difference was observed between anodal, cathodal, or sham tDCS treatments in 21 patients. Recently, in 2019, Garcia-Larrea et al (3) reported that 6 out of 12 NP patients with various conditions (e.g., CPSP, SCI, or BPI) achieved satisfactory changes in pain intensity. This study demonstrated that 20 sessions of tDCS over the M1 (2 mA, 20 min) were safe and provided long-lasting pain relief.…”
Section: Neuropathic Pain Of Other Various Originsmentioning
confidence: 99%
“…patients are non-responsive to conventional analgesics, which include non-steroidal anti-inflammatory drugs, anticonvulsants, or antidepressants. In such cases, neuromodulation treatments such as repetitive transcranial magnetic stimulation (rTMS), transcranial direct current stimulation (tDCS), and deep brain stimulation, are applied for the treatment of NP (3).…”
mentioning
confidence: 99%